Lexical development in an Indonesian-Balinese bilingual child - Ni Luh Putu Sri Adnyani; Ni Made Rai Wisudariani; I Wayan Swandana (Indonesian Journal of Applied Linguistics, 2022)
It is debatable whether bilingual children can distinguish between their two languages from an early age. This study aims to describe how a bilingual infant differentiates between her two languages, focusing on the acquisition of a dual vocabulary. This topic is addressed in a bilingual case study of an infant who acquired a national language (Indonesian) and an indigenous language (Balinese) simultaneously from birth until the age of one year and eleven months. Within the family, the two languages are used interchangeably. The parents' native language is Balinese, and Indonesian is the neighbourhood’s lingua franca. However, within the peer group, Indonesian is the dominant language. Daily diaries are used to record the child's vocabulary development in combination with weekly video recordings in the two language settings. The study shows that the child develops vocabulary in both Indonesian and Balinese. Since Indonesian and Balinese are closely related, the child also develops words that are shared by the two languages. During the development of the child’s vocabulary, Indonesian words outnumbered Balinese words due to the dominant use of Indonesian in the environment. The research demonstrates that translation equivalents (TEs) mean those language choices are available from the early stages of language development. The study shows that translation equivalents (TEs) demonstrate those language choices are available from the initial stages of language development. The findings highlight that a child who is exposed to two closely related languages can differentiate different language systems from an early age. Despite the child's ability to differentiate between the two languages, the national language develops at a far quicker rate than the indigenous language.